Social harms in female-initiated HIV prevention method research: state of the evidence. (15th November 2019) - Montgomery, Elizabeth T.; Roberts, Sarah T.; Nel, Annalene; Malherbe, Mariette; Torjesen, Kristine; Bunge, Katherine; Singh, Devika; Baeten, Jared M.; Marrazzo, Jeanne; Chirenje, Z. Mike; Kabwigu, Samuel; Beigi, Richard; et al.
Abstract : Objectives: Assessment of safety is an integral part of real-time monitoring in clinical trials. In HIV prevention research, safety of investigational products and trial participation has been expanded to include monitoring for 'social harms', generally defined as negative consequences of trial participation that may manifest in social, psychological, or physical ways. Further research on social harms within HIV prevention research is needed to understand the potential safety risks for women and advance the implementation of prevention methods in real-world contexts. Methods: Secondary analysis of quantitative data from three randomized, double-blind, placebo-controlled trials of microbicide candidates in sub-Saharan Africa was conducted. Additionally, we assessed data from two prospective cohort studies that included participants who became HIV-positive or pregnant during parent trials. Results: Social harms reporting was low across the largest and most recent microbicide studies. Social harm incidence per 100 person-years ranged from 1.10 (95% CI 0.78–1.52) to 3.25 (95% CI 2.83–3.74) in the phased trials. Reporting differed by dosing mechanism (e.g. vaginal gel, oral tablet, ring) and study, most likely as a function of measurement differences. Social harms were most frequently associated with male partners, rather than, for example, experiences of stigma in the community. Conclusion: Measurement and screening for social harms is an important component of conducting ethical research of novel HIV prevention methods. To date, social harm incidence reported in microbicide trials has been relatively low (<4% per 100 person-years), and the majority have been partner-related events. However, any incidence of social harm within the context of HIV prevention is important to capture and understand for the safety of individuals, and for the successful impact of prevention methods in a real-world context.